Financial Transmission Mechanism between Financial Centers and Peripheries - Masujima, Yuki (The Indonesian Capital Market Review, 2010)
The causes of contagion effects during periods of crisis are still unable to be fully explained by fundamental factors. This paper focuses on non-fundamental explanatory factors such as inancial centers' shock ampliication effects induced by global portfolio investors and extends Kaminsky and Reinhart (2003)'s center-periphery framework by introducing three time zones for the analysis of conditional distribution of 37 countries' daily stock returns from 1994 to 2003, and accessibility of stock markets to investigate if inancial centers stabilize or amplify shocks. Centers such as U.S. and Germany played a vital role in propagating turmoil in G7 countries and spreading shocks to countries in other regions during periods of crisis, whereas Japan ampliied turmoil in Asian peripheries only within the same region. In contrast, an emerging center, Hong Kong, appears to have much stronger shock-ampliication effects on developing countries than the three centers